Possibilities of conservative treatment of patients with lymphedema of the extremities (literature review) - P. N. Myshentsev; G. V. Yarovenko; S. E. Katorkin (Бюллетень сибирской медицины)
The literature review describes various methods for treating patients with lymphedema of the extremities. Statistics show an increase in the incidence and disability of patients with this pathology. However, the possibilities of therapeutic measures in lymphedema are far from perfect.The analysis of literature data showed that the basis of treatment for lymphedema of the extremities is comprehensive conservative therapy with the use of pathogenetically grounded physical, mechanical, and medical methods. In complex schemes of conservative treatment for lymphedema, physiotherapy methods occupy a prominent place. The most common technique among them is regular combined decongestive therapy. This method is recognized by leading experts as the main one in treating patients with lower extremity lymphedema. Commitment of patients to treatment and their social and psychological counseling are of great importance. The choice of the volume and method of surgical intervention requires a difficult and individual assessment of pathological changes developing throughout the course of the disease.Despite certain improvements in treatment methods, lower extremity lymphedema is still an unsolved issue. The experience of most specialists involved in lymphedema treatment demonstrates a reasonable balance between basic conservative and surgical treatment methods. Undoubtedly, results of evaluation of these methods will improve the choice of an optimal technique for treating patients with lymphedema of the extremities.